5
$\begingroup$

Assume that $\{\alpha, \beta, \gamma\} \subset \left[0,\frac{\pi}{2}\right]$, $\sin\alpha+\sin\gamma=\sin\beta$ and $\cos\beta+\cos\gamma=\cos\alpha$.

Try to find a value of $\alpha-\beta$.

Actually I have gotten that $\alpha+2\gamma+\beta=\pi$ and $\sin2\alpha+\sin2\beta=\sin(\alpha+\beta)$, $\cos2\alpha+\cos2\beta=\cos(\alpha+\beta)$

But I can't get further more.

$\endgroup$
  • $\begingroup$ I fixed the MathJax for the functions. $\endgroup$ – Claude Leibovici Sep 9 '17 at 8:57
2
$\begingroup$

We have $$\sin 2\alpha+\sin2\beta=\sin(\alpha+\beta)$$ and $$\cos2\alpha+\cos2\beta=\cos(\alpha+\beta)$$ So by squaring and then adding the above equations, we get $$(\sin2\alpha+\sin2\beta)^2+(\cos2\alpha+\cos2\beta)^2=\sin^2(\alpha+\beta)+\cos^2(\alpha+\beta)$$ $$\Rightarrow \sin^22\alpha+\sin^22\beta+2\sin2\alpha\sin2\beta+\cos^22\alpha+\cos^22\beta+2\cos2\alpha\cos2\beta=1$$ $$\Rightarrow2\sin2\alpha\sin2\beta+2\cos2\alpha\cos2\beta+2=1$$ $$\Rightarrow\sin2\alpha\sin2\beta+\cos2\alpha\cos2\beta=-\frac12$$ Now we know that $\cos x\cos y+\sin x\sin y=\cos(x-y)$. So $$\cos(2\alpha-2\beta)=-\frac12$$ $$\Rightarrow2\alpha-2\beta=\frac{2\pi}{3}$$ $$\alpha -\beta=\frac\pi3\ rad=60^\circ$$

$\endgroup$
3
$\begingroup$

we have $$\sin(\gamma)=\sin(\beta)-\sin(\alpha)$$ and $$\cos(\gamma)=\cos(\alpha)-\cos(\beta)$$ squaring and adding both we get $$-1=-2(\cos(\alpha)\cos(\beta)+\sin(\alpha)\sin(\beta))$$ therefore we obtain $$\cos(\alpha-\beta)=\frac{1}{2}$$

$\endgroup$
  • $\begingroup$ So it looks like that the describe of the problem is not right. $\endgroup$ – Intoks Liobein Sep 9 '17 at 9:08
  • $\begingroup$ why that? you can compute $$\alpha-\beta$$ now from the last line $\endgroup$ – Dr. Sonnhard Graubner Sep 9 '17 at 9:10
  • $\begingroup$ But 2\pi/3 is larger than \pi/2 $\endgroup$ – Intoks Liobein Sep 9 '17 at 9:11
  • $\begingroup$ on moment i will look at my calculations $\endgroup$ – Dr. Sonnhard Graubner Sep 9 '17 at 9:19
  • $\begingroup$ sorry i forgot the minus sign $\endgroup$ – Dr. Sonnhard Graubner Sep 9 '17 at 9:23
1
$\begingroup$

$$1=\sin^2\gamma+\cos^2\gamma=(\sin\beta-\sin\alpha)^2+(\cos\alpha-\cos\beta)^2=2-2\cos(\alpha-\beta).$$ Thus, $$\cos(\alpha-\beta)=\frac{1}{2}.$$ In another hand, $$\sin\gamma=\sin\beta-\sin\alpha\geq0,$$ which says $\beta\geq\alpha.$

Id est, $\alpha-\beta=-60^{\circ}$ and we are done!

$\endgroup$
  • $\begingroup$ @Intoks Liobein Why did you accepted a wrong solution? Maybe have you a question about my solution? I am ready to explain. $\endgroup$ – Michael Rozenberg Oct 10 '17 at 7:31
-1
$\begingroup$

If you have $$\sin2\alpha+\sin2\beta=\sin(\alpha+\beta) \to 2\sin(\alpha+\beta)\sin(\alpha-\beta)=\sin(\alpha+\beta)$$and $$\cos2\alpha+\cos2\beta=\cos(\alpha+\beta)\to \cos(\alpha+\beta)\cos(\alpha-\beta)=\cos(\alpha+\beta) $$divide them $$\frac{2\sin(\alpha+\beta)\sin(\alpha-\beta)}{2\cos(\alpha+\beta)\cos(\alpha-\beta)}=\frac{\sin(\alpha+\beta)}{\cos(\alpha+\beta)}\\\to \tan(\alpha-\beta)=1 \to \alpha-\beta=\frac{\pi}{4}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.